Different Stratification of Physiological Factors Affecting Cerebral Perfusion Pressure in Hypoxic-Ischemic Brain Injury after Cardiac Arrest According to Visible or Non-Visible Primary Brain Injury: A Retrospective Observational Study - Changshin Kang (MDPI AG, 2021)
We aimed to explore the stratification of physiological factors affecting cerebral perfusion pressure, including arterial oxygen tension, arterial carbon dioxide tension, mean arterial pressure, intracranial pressure (ICP), and blood-brain barrier (BBB) status, with respect to primary or secondary brain injury (PBI or SBI) after out-of-hospital cardiac arrest (OHCA). Among the retrospectively enrolled 97 comatose OHCA survivors undergoing post-cardiac arrest (PCA) care, 46 (47.4%) with already established PBI (high signal intensity (HSI) on diffusion-weighted imaging (DWI) had higher ICP (p = 0.02) and poorer BBB status (p < 0.01) than the non-HSI group. On subgroup analysis within the non-HSI group to exclude the confounding effect of already established PBI, 40 (78.4%) patients with good neurological outcomes had lower ICP at 24 h (11.0 vs. 16.0 mmHg, p < 0.01) and more stable BBB status (p = 0.17 in pairwise comparison) compared to those with poor neurological outcomes, despite the non-significant differences in other physiological factors. OHCA survivors with HSI on DWI showed significantly higher ICP and poorer BBB status at baseline before PCA care than those without HSI. Despite the negative DWI findings before PCA care, OHCA survivors have a cerebral penumbra at risk for potentially leading the poor neurological outcome from unsuppressed SBI, which may be associated with increased ICP and BBB permeability.